2018
DOI: 10.5812/jhealthscope.14134
|View full text |Cite
|
Sign up to set email alerts
|

Indicators of Organizational Resilience in Critical Sociotechnical Systems: A Qualitative Study for the Refinery Complex

Abstract: Background: Resilience engineering is a new approach for safety management. The purpose of this paper was to determine indicators constructing organizational resilience as an important part of overall resilience. Methods: This was a qualitative study. The data collection method was semi-structured interviews as well as the discussion group method. The data were analyzed with conventional qualitative content analysis. Results: Overall, 232 primary codes were classified in 81 sub-indicators and 11 indicators. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…According to the experts, senior management commitment is one of the organizational factors that affect resilience and is the main factor of success for safety plans. 31 The just culture has been ranked second and this represents that top managers have provided a safe environment for workers so that they can easily report incidents and mistakes to the authorities. Pinion et al pointed out that top management commitment to safety increases self-reporting among workers.…”
Section: Discussionmentioning
confidence: 99%
“…According to the experts, senior management commitment is one of the organizational factors that affect resilience and is the main factor of success for safety plans. 31 The just culture has been ranked second and this represents that top managers have provided a safe environment for workers so that they can easily report incidents and mistakes to the authorities. Pinion et al pointed out that top management commitment to safety increases self-reporting among workers.…”
Section: Discussionmentioning
confidence: 99%
“…The highest cited paper is 'Resilience and brittleness in the offshore helicopter transportation system: The identification of constraints and sacrifice decisions in pilots' (Gomes et al, 2009) with 54 citations by the end of 2021. By comparison, Shirali GA, whose publications mainly concentrated on the period 2012-2018, carrying out resilience research with different backgrounds using quantitation-based methods, e.g., process industry, drilling company, petrochemical plant, chemical plant, and hospital (Shirali et al, 2018(Shirali et al, , 2016b(Shirali et al, , 2012a(Shirali et al, , 2016b(Shirali et al, , 2012bNodoushan et al, 2017;Jafari et al, 2018Jafari et al, , 2013Arassi et al, 2015). One of his publications entitled "A new method for quantitative assessment of resilience engineering by PCA and NT approach: A case study in a process industry" received 81 citations.…”
Section: Authors Outputs and Collaborationmentioning
confidence: 99%
“…(Shirali and Nematpour, 2019), which is consistent with the results of the present paper. In another work done by (Jafari et al, 2018), senior management commitment was determined as one of the effective criteria in resilience of a system and one of the main factors in success of safety planning. Considering the results of the present work and its consistency with above mentioned research, it can be concluded that in order to improve resilience level and health, safety, and environmental condition of an organization, most effort should be employed to change senior managers' attitude.…”
Section: Generating Decision Matrixmentioning
confidence: 99%